Extensive respiratory chain defects in inhibitory interneurones in patients with mitochondrial disease. (30th May 2015) - Lax, Nichola Z.; Grady, John; Laude, Alex; Chan, Felix; Hepplewhite, Philippa D.; Gorman, Grainne; Whittaker, Roger G.; Ng, Yi; Cunningham, Mark O.; Turnbull, Doug M.
Abstract : Aims: Mitochondrial disorders are among the most frequently inherited cause of neurological disease and arise due to mutations in mitochondrial or nuclear DNA. Currently, we do not understand the specific involvement of certain brain regions or selective neuronal vulnerability in mitochondrial disease. Recent studies suggest γ‐aminobutyric acid (GABA)‐ergic interneurones are particularly susceptible to respiratory chain dysfunction. In this neuropathological study, we assess the impact of mitochondrial DNA defects on inhibitory interneurones in patients with mitochondrial disease. Methods: Histochemical, immunohistochemical and immunofluorescent assays were performed on post‐mortem brain tissue from 10 patients and 10 age‐matched control individuals. We applied a quantitative immunofluorescent method to interrogate complex I and IV protein expression in mitochondria within GABAergic interneurone populations in the frontal, temporal and occipital cortices. We also evaluated the density of inhibitory interneurones in serial sections to determine if cell loss was occurring. Results: We observed significant, global reductions in complex I expression within GABAergic interneurones in frontal, temporal and occipital cortices in the majority of patients. While complex IV expression is more variable, there is reduced expression in patients harbouring m.8344A>G point mutations and POLG mutations. In addition to the severe respiratory chain deficiencies observed in remaining interneurones, quantification of GABAergic cell density showed a dramatic reduction in cell density suggesting interneurone loss. Conclusions: We propose that the combined loss of interneurones and severe respiratory deficiency in remaining interneurones contributes to impaired neuronal network oscillations and could underlie development of neurological deficits, such as cognitive impairment and epilepsy, in mitochondrial disease. Abstract : Reduced expression of mitochondrial respiratory chain components may give rise to the selective vulnerability of GABAergic interneurons in mitochondrial disease and contribute to neurological impairment.